Epidemiological trends and determinants of mumps outbreaks: a systematic review and meta-analysis - Agrawal, Ritik; Rehman, Tanveer; Sinha, Deepti; Chakraborty, Poulomee; Sakthivel, Manikandanesan; Kumar, Dewesh; Mitra, Srijeeta; Karumathil, Afeeq; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Public Health, 2025)
BackgroundDespite widespread vaccination programs, mumps has resurged globally. This systematic review and meta-analysis assessed the epidemiological characteristics, attack rates (ARs), and complications of mumps outbreaks worldwide from 2004 to 2024.MethodsWe systematically searched MEDLINE, Embase, CINAHL and Google Scholar for studies reporting on mumps outbreaks. Confirmed mumps cases, defined by WHO criteria, were included across all age groups. Epidemiological characteristics were summarized using the Time-Place-Person format. Pooled ARs and complication rates were calculated using random-effects models. Subgroup analyses examined variations by age, region, vaccination status, and outbreak period. A random-effects meta-regression and leave one out sensitivity analysis was used to explore the influence of study-level characteristics heterogeneity in the attack rate among mumps outbreak studies. Heterogeneity was assessed using Cochran’s Q and I2, and publication bias was evaluated with funnel plots and Egger’s test.ResultsA total of 47 studies from 21 countries reporting 71,174 mumps cases, were included in the systematic review, with 30 studies in the meta-analysis. The pooled AR of mumps outbreaks was 14.5% (95% CI: 12.91–16.11), with adults having the highest AR (31.8%). The pooled complication rate was 10.3% (95% CI: 5.7–14.9), with orchitis being the most common complication (63.1%). Temporal trends showed peaks during 2004–2009 and 2016–2020, while regional analysis revealed higher ARs in the Americas (29.2%) and Eastern Mediterranean (28.8%) regions compared to Europe (7.6%) and South-East Asia (9.6%). Among vaccinated individuals, ARs were highest with a single dose (35.7%) and lowest with three doses (10.1%).ConclusionMumps outbreaks remain a global concern due to waning vaccine-induced immunity. Incorporating a third MMR booster dose into vaccination schedules is recommended, particularly for high-risk groups, to reduce ARs and complications effectively.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.